İmâm-ı Rabbânî'ye göre vahdet-i vücûd ve vahdet-i şuhûd - (:unkn) unknown (My University, 2009)
İmâm-ı Rabbânî Ahmed Sihrindî vahdet-i vücûd konusunu ele alıp tartışmış, bu düşünceye bazı eleştiriler yöneltmiş ve vahdet-i şuhûd teorisini geliştirmiştir. Ona göre vahdet-i vücûd, tasavvuf yolunda ulaşılması ve aşılması gereken bir mertebedir. O mertebenin üzerinde vahdet-i şuhûd isminde yeni bir mertebe ve idrak seviyesi vardır. Bu makalede İmâm-ı Rabbânî‟nin vahdet-i vücûd ve vahdet-i şuhûd konusundaki fikirleri incelenmiştir.

Imam-i Rabbani Ahmad Sirhindi who was one of the eminent Sufis of India elaborated and criticised the theory of unity of being (vahdat-i vujud). He also developed the theory of unity of vision (vahdat-i shuhud). Accordding to him, unity of being is a state that must be reached and passed in Sufi way. Unity of vision is higher than unity of being. This article indicates Imam-i Rabbani‟s point of view on this subject.
Unity of being and unity of vision according to Imam-i Rabbani
Keywords: Din Bilimi